Joint Shear Deformation and Beam Rotation in RC Beam-Column Eccentric Connections - Ullah, Rooh; Fahim, Muhammad; Nouman, Muhammad (Salehan Institute of Higher Education, 2021)
This paper discusses joint shear deformation and beam rotation for RC beam-column eccentric connections. Two eccentric connections were designed according to ACI 318-14 and ACI-352 and their half scaled models were constructed sequentially to introduce a cold joint at the beam column interface. Specimen having eccentricity equal to bc/8 (12.5% of column width) and bc/4 (25% of column width) were named as specimen 1 and specimen 2 respectively. The specimens were tested under quasi static full cyclic loading. The results are presented in the form of beam rotation versus drift and beam rotation versus lateral load plots. In addition, joint shear deformation versus drift is also plotted for both specimens. Careful observation of the damage pattern revealed that bond slip occurred at 2.5% drift in both specimens with no yielding of beam longitudinal bars in the joint core due to the presence of construction joint. An increase in out of plane rotation was observed with increase in eccentricity. However, in plane rotation was more in specimen 1 as compared to specimen 2, primarily due to negligible out of plane rotations. Furthermore, joint shear deformation increased with increase in eccentricity. However, it was negligible due to slab contribution as well as bond slippage with minimum load transfer to the joint core. It is concluded that bond slippage is the principal failure pattern whereas out of plan rotation increases with eccentricity without significant contribution to the final failure pattern.Â Doi: 10.28991/cej-2021-03091650 Full Text: PDF